MULTIMEDIA-BASED PRESENTATION AND SELF-CONFIDENCE ANALYSIS: A QUANTITATIVE STUDY ON ENGLISH LANGUAGE LEARNING OF VOCATIONAL COLLEGE STUDENTS - Indrayanti, Iin (LLT Journal: A Journal on Language and Language Teaching, 2021)
Technology using multimedia assistance is expected to be able to boost some changes both in the classroom atmosphere in general and individual in particular either cognitive (learning outcomes) or affective (learning attitudes). One of learning media that is well-known among users in education is multimedia presentations or Power Point which combine text, graphics, images, photos, audio, videos, and animation in an integrated manner. One of learning tools featuring those conveniences is Genially. The current study was preliminary in nature regarding the use of Genially online media presentation and to investigate with respect its influence on self-confidence among male and female students. The study focused on one skill of language in delivering selected topic or idea using English. Using a quantitative approach, this study involved 62 students consisting of 42 males and 20 females of sophomore students from one vocational college in a small city in Indonesia. To determine level of self-confidence, students were given a questionnaire responding 12 statements in 4 answer scales. Output of One Way Anova and regression test calculation showed that the use of PowerPoint Genially influenced self-confidence for both genders. Even though this media was capable to lead more pleasant and enjoyable learning atmosphere, the influence performed by the variables was considered less significant. This means that students still feel less confident to use oral English in delivering selected topics to their friends in the class.